Understanding Knowledge Sharing Behavior: An Examination of the Extended Model of Theory of Planned Behavior - Sabrina O. Sihombing (The Winners, 2011)
Knowledge is recognized as one valuable asset for many organizations. Thus, knowledge-sharing is one of important activities in many organizations, including university. Knowledge sharing is defined as activities of transferring or disseminating organizationally relevant information, ideas, suggestions, and expertise with one another. This research applied Christian values as a moderating variable in the framework of theory of planned behavior. The aims of this research to assess applicability of the theory of planned behavior to predict knowledge sharing and to examine the effects of Christian values in the relationship between attitude and intention to share knowledge. A self-administered questionnaire was used to collect the data for this study. The data was then analyzed using structural equation modeling.